Perancangan Alat Monitoring Ketinggian Air Sungai Berbasis NODEMCU Esp8266 Terintegrasi Platform Website (Universitas (STKIP) PGRI Sumatera Barat, 2022)
Along with the volume of water that often increases suddenly resulting in a lot of losses that are felt from the overflow, resulting in flooding during the rainy season or sending water from highland areas which can cause the volume of water in the river to be unpredictable, this makes it difficult for people to avoid and anticipate early the impact of the overflowing river or the flood disaster. In this case, a system is needed that is designed to inform the water level in real time in order to monitor and bind the public's awareness of overflowing water so that early action can be taken to save and tidy up items that are sensitive to water, through the Design of a Real Water Level Monitoring Tool. Time and integration with web-based applications can be done to find out early on the water level in real time and can be accessed by all people in the area around riverbanks to be more alert, especially during the rainy season.